Morphological and physiological variation in Toona ciliata under water and salinity stress Variação morfológica e fisiológica em Toona ciliata sob efeito de estresse hídrico e salino - de Andrade R.S.* (2020)
© 2020, Universidade Federal de Santa Maria. All rights reserved.The objective of this paper was to test the effects of water deficit, saturation and salinity in individuals of Toona ciliata. Seven treatments were tested: the control group, the complete suspension of irrigation, the permanent saturation of the pot soil and four doses of NaCl (50, 100, 200 and 400 µmol). The experimental design was completely randomized, with 8 repetitions in each treatment. Physiologic evaluations were carried out during the experiment, and morphologic evaluations at the end. The plants were responsive to the applied stresses comparatively to the control group. Reductions were observed in morphological and physiological variables in all treatments under stress. All individuals under stress recovered slightly in the end of the experiment, and began to sprout again, representing a probable adaptation to the conditions.